Significant association between the C(−1019)G functional polymorphism of the HTR1A gene and impulsivity - Benko, Anita; Lazary, Judit; Molnar, Eszter; Gonda, Xenia; Tothfalusi, Laszlo; Pap, Dorottya; Mirnics, Zsuzsanna; Kurimay, Tamas; Chase, Diana; Juhasz, Gabriella; Anderson, Ian M.; Deakin, John F.W.; et al. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2010)
Serotonin‐1A (5‐HT1A) receptors are known to play a role in impulsivity‐related behavior. The C(−1019)G functional polymorphism (rs6295) has been suggested to regulate the 5‐HT1A receptor gene (HTR1A) expression in presynaptic raphe neurons, namely, increased receptor concentration and reduced neuronal firing could be associated with the G allele. Previous studies indicate that this polymorphism is associated with aggression, suicide, and several psychiatric disorders, yet its association with impulsivity has rarely been investigated. We studied the relationship between impulsivity and the C(−1019)G polymorphism of the HTR1A in a population sample of 725 volunteers using the Impulsiveness subscale (IVE‐I) of the Eysenck Impulsiveness, Venturesomeness, and Empathy scale and also the Barratt Impulsiveness Scale (BIS‐11). Data were analyzed using analysis of variance with age and gender as covariates and Tukey's HSD post‐hoc test. Post‐hoc analysis revealed that the study had 0.958 power to detect 0.15 effect size. Significant differences between the C(−1019)G genotype groups (GG vs. GC vs. CC) were found. Subjects carrying GG genotype showed significantly higher impulsiveness scores compared to GC or CC carriers for the IVE‐I scale (P = 0.014), for the Motor (P = 0.021), Cognitive Impulsiveness (P = 0.002), and for the BIS total score (P = 0.008) but not for the Nonplanning Impulsiveness (P = 0.520) subscale of the BIS‐11. Our results suggest the involvement of the HTR1A in the continuum phenotype of impulsivity. © 2009 Wiley‐Liss, Inc.